2016
DOI: 10.5455/ijmsph.2016.11102015147
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Desarda repair in inguinal hernia: a study in northern part of Bangladesh

Abstract: Background: Inguinal hernia repair by Desarda method provides a new concept of repair maintaining the physiology of inguinal canal. Repair without mesh gives another benefit of cost-effectiveness and freeing of foreign body-related complications. Objective: To observe the outcome of inguinal hernia repair by Desarda method as an alternative to most popular Lichtenstein repair. Materials and Methods: The longitudinal study was conducted from July 2012 to June 2015. A total of 184 patients with uncomplicated ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
4
2
Order By: Relevance
“…Mean age was 45.42 years, SD ±10.08. 8 The mean age in current study was lesser when compared with above cited study. They further reported that at 1 st post-operative day, total 73 patients found with mild pain and 98.37% patients had no complaint of chronic pain.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Mean age was 45.42 years, SD ±10.08. 8 The mean age in current study was lesser when compared with above cited study. They further reported that at 1 st post-operative day, total 73 patients found with mild pain and 98.37% patients had no complaint of chronic pain.…”
Section: Discussioncontrasting
confidence: 59%
“…Inguinal hernia repairs with this method are less expensive and devoid of difficulties brought on by foreign bodies. 5,6 In their study on Desarda's repair published in2016, Roy and coworkers found that the majority of patients(168/168;91.30%) experienced only minor pain on the third post-operative day and only 73/73(39.67%; VAS) individuals experienced only mild pain on the 1 st post-operative day (VAS). 5 According to Bhatti and colleagues, Desarda's technique took 28.90 5.57 minutes to complete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the patients operated by Desarda repair are of low socioeconomic status. 11 Rodriguez, et al proved in his study that Desarda takes more time than Lichtenstein (48 vs. 39 min) and it was statistically significant P <.05. (6) This time is very less as compared to our study.…”
Section: Discussionmentioning
confidence: 90%
“…Abbas et al (10) reported at least twenty patients have experienced some sort of postoperative problem Pneumonias (lobar or bronchopneumonia) accounted for 20% of cases, as did sepsis syndrome (14%), and infections of local wounds (6 percent). Roy et al (11) also found comparable results, 184 cases were treated with Desarda technique, out of them 12 cases had postoperative complications, particularly 7 cases had developed wound infection, seroma was in 3 cases and hematoma in 2 cases, furthermore they reported that one patient had developed recurrent inguinal hernia.…”
Section: Discussionmentioning
confidence: 77%